Enzymatic crosslinking and food allergenicity: A comprehensive review. Issue 6 (15th October 2021) - Ahmed, Ishfaq; Chen, Huan; Li, Jiale; Wang, Bin; Li, Zhenxing; Huang, Gonghua
Abstract: Food allergy has become a major global public health concern. In the past decades, enzymatic crosslinking technique has been employed to mitigate the immunoreactivity of food allergens. It is an emerging non‐thermal technique that can serve as a great alternative to conventional food processing approaches in developing hypoallergenic food products, owing to their benefits of high specificity and selectivity. Enzymatic crosslinking via tyrosinase (TYR), laccase (LAC), peroxidase (PO), and transglutaminase (TG) modifies the structural and biochemical properties of food allergens that subsequently cause denaturation and masking of the antigenic epitopes. LAC, TYR, and PO catalyze the oxidation of tyrosine side chains to initiate protein crosslinking, while TG initiates isopeptide bonding between lysine and glutamine residues. Enzymatic treatment produces a high molecular weight crosslinked polymer with reduced immunoreactivity and IgE‐binding potential. Crosslinked allergens further inhibit mast cell degranulation due to the lower immunostimulatory potential that assists in the equilibration of T‐helper (Th)1/Th2 immunobalance. This review provides an updated overview of the studies carried out in the last decade on the potential application of enzymatic crosslinking for mitigating food allergenicity that can be of importance in the context of developing hypoallergenic/non‐allergenic food products.